Research Anthology on Facilitating New Educational Practices Through Communities of Learning 2021
DOI: 10.4018/978-1-7998-7294-8.ch032
|View full text |Cite
|
Sign up to set email alerts
|

Teachers Learning to Teach English Learners in an Online Community of Practice in an Urban District

Abstract: This chapter reports on a study that investigated the knowledge and skills for teaching English learners (ELs) that in-service teachers displayed during their participation in an online community of practice. Teachers' conversations were analyzed using a priory and inductive codes. Findings showed that teachers demonstrated an understanding of practices that support ELs in overcoming language demands that disciplinary content standards in the U.S. pose, including promoting ELs' participation, teaching language… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…The inequity issues in our school with ELLs could be further understood from the perspective of teacher quality in the classroom. This study interrogates public school teachers' preparedness during their first years of teaching for these demographic changes.Prior research suggests that teachers' feelings of preparedness may differ by whether they work with ELLs (De Jong & Harper, 2005;del Rosal et al, 2018;Gandara et al, 2005;Reeves, 2009). Research has also shown that teachers are not being prepared to meet the needs for a diverse population in US classrooms today (e.g., Robertstein and Lee, 2014).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The inequity issues in our school with ELLs could be further understood from the perspective of teacher quality in the classroom. This study interrogates public school teachers' preparedness during their first years of teaching for these demographic changes.Prior research suggests that teachers' feelings of preparedness may differ by whether they work with ELLs (De Jong & Harper, 2005;del Rosal et al, 2018;Gandara et al, 2005;Reeves, 2009). Research has also shown that teachers are not being prepared to meet the needs for a diverse population in US classrooms today (e.g., Robertstein and Lee, 2014).…”
mentioning
confidence: 99%
“…Prior research suggests that teachers' feelings of preparedness may differ by whether they work with ELLs (De Jong & Harper, 2005;del Rosal et al, 2018;Gandara et al, 2005;Reeves, 2009). Research has also shown that teachers are not being prepared to meet the needs for a diverse population in US classrooms today (e.g., Robertstein and Lee, 2014).…”
mentioning
confidence: 99%